2018
DOI: 10.1101/486480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oral thermosensing by murine trigeminal neurons: modulation by capsaicin, menthol, and mustard oil

Abstract: Key pointsr Orosensory thermal trigeminal afferent neurons respond to cool, warm, and nociceptive hot temperatures with the majority activated in the cool range.r Many of these thermosensitive trigeminal orosensory afferent neurons also respond to capsaicin, menthol, and/or mustard oil (allyl isothiocyanate) at concentrations found in foods and spices.r There is significant but incomplete overlap between afferent trigeminal neurons that respond to oral thermal stimulation and to the above chemesthetic compound… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 68 publications
(99 reference statements)
8
23
0
Order By: Relevance
“…Additionally, we monitored only the surface of DRG using confocal microscopy, and it is possible that the actual cell number activated by mild stimuli like large brush would be greater if we could image deeper into the DRG. Other groups and our own results also showed that the activated cell number is different depending on the stimulus in in vivo DRG and trigeminal ganglia Ca 2+ imaging (Kim et al, 2016;Chisholm et al, 2018;Leijon et al, 2019). More detailed analysis reveals that the increased cell number following plantar incision is mainly due to an increase in small to medium diameter cells.…”
Section: β -Iiisupporting
confidence: 57%
“…Additionally, we monitored only the surface of DRG using confocal microscopy, and it is possible that the actual cell number activated by mild stimuli like large brush would be greater if we could image deeper into the DRG. Other groups and our own results also showed that the activated cell number is different depending on the stimulus in in vivo DRG and trigeminal ganglia Ca 2+ imaging (Kim et al, 2016;Chisholm et al, 2018;Leijon et al, 2019). More detailed analysis reveals that the increased cell number following plantar incision is mainly due to an increase in small to medium diameter cells.…”
Section: β -Iiisupporting
confidence: 57%
“…This suggests that if koku sensations are indeed transmitted via somatosensory afferent of the trigeminal ganglion, there is not a uniform group of "koku-responding" neurons in that ganglion. Moreover, the relatively small population of trigeminal ganglion neurons dedicated to oral stimulation with kokumi substances (for instance compared with thermal-orosensitive neurons, Leijon et al 2019) suggest that it will remain a challenge to study koku-evoked somatosensations at the cellular level in the trigeminal ganglion. In particular, relating kokuresponsive neurons to molecular markers and eventually identifying a molecular receptor in trigeminal neurons will be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…We used transgenic mice that express the calcium indicator GCaMP3 or GCaMP6s in sensory neurons, including those in the trigeminal ganglion (Leijon et al, 2019). GCaMP3 mice were obtained from X. Dong, Johns Hopkins and express GCaMP3 as a knock-in/knockout at the Pirt locus (Kim, Chu et al, 2014).…”
Section: Animal Modelmentioning
confidence: 99%
See 2 more Smart Citations